Review on Public Health Effects of Aflatoxins in Milk and Milk-Based Foodstuffs of Dairy Cow - Zakir Abadura Sadik; Abdo Jilo Sufian; Abdurahman Mukarim; Kumar PNair Suresh (Journal of Veterinary Healthcare, 2022)
Aflatoxins are toxigenic metabolites that are definitely occurring by lethal strains of Aspergillus parasiticus and Aspergillus flavus that commonly dwell and colonize in feed components and various nutritive foodstuffs particularly milk and milk based products. This Review has three main objectives; those are causes of aflatoxin, effects and methods of control in milk and milk products. Drinking of cow milk polluted with aflatoxin may overwhelm immunity and subsidize to stunting in young children, as the young children are not immune-competent during early stage. It has been internationally assessed that aflatoxin is possibly accountable for 30% of the annual cases of liver cancer. Generally, control approaches of aflatoxin can be applied during pre-harvest, cautious management in the time of harvest and postharvest decontamination. Moreover, choosing breed for aflatoxin impervious crop diversities, prevention of aflatoxin production through biological decontamination by microorganisms and their metabolites, rejection of aflatoxin by physical means in addition to inactivation by chemicals are the typical approaches that have been described in different studies. For the reason that cow milk is the most important and principal diet of children, but the risk of exposed to the cancer are more in infants. In addition, according to various investigations it also well thought that young animals are also found to be more vulnerable to aflatoxin than adults. Thus; the contamination of cow milk and milk products by AFM1 should understood as undesirable for young human and animals.
Keywords: Aflatoxin